Expression of a radish defensin in transgenic wheat confers increased resistance to Fusarium graminearum and Rhizoctonia cerealis - Li, Zhao; Zhou, Miaoping; Zhang, Zengyan; Ren, Lijuan; Du, Lipu; Zhang, Boqiao; Xu, Huijun; Xin, Zhiyong (Functional & integrative genomics, 2011)
Fusarium head blight (scab), primarily caused by Fusarium graminearum, is a devastating disease of wheat (Triticum aestivum L.) worldwide. Wheat sharp eyespot, mainly caused by Rhizoctonia cerealis, is one of the major diseases of wheat in China. The defensin RsAFP2, a small cyteine-rich antifungal protein from radish (Raphanus sativus), was shown to inhibit growth in vitro of agronomically important fungal pathogens, such as F. graminearum and R. cerealis. The RsAFP2 gene was transformed into Chinese wheat variety Yangmai 12 via biolistic bombardment to assess the effectiveness of the defensin in protecting wheat from the fungal pathogens in multiple locations and years. The genomic PCR and Southern blot analyses indicated that RsAFP2 was integrated into the genomes of the transgenic wheat lines and heritable. RT-PCR and Western blot proved that the RsAFP2 was expressed in these transgenic wheat lines. Disease tests showed that four RsAFP2 transgenic lines (RA1-RA4) displayed enhanced resistance to F. graminearum compared to the untransformed Yangmai 12 and the null-segregated plants. Assays on Q-RT-PCR and disease severity showed that the express level of RsAFP2 was associated with the enhanced resistance degree. Two of these transgenic lines (RA1 and RA2) also exhibited enhanced resistance to R. cerealis. These results indicated that the expression of RsAFP2 conferred increased resistance to F. graminearum and R. cerealis in transgenic wheat.